FAKTOR â FAKTOR YANG MEMPENGARUHI TINGKAT FERTILITAS DI KELURAHAN BANDARJO DAN DESA KEJI KECAMATAN UNGARAN BARAT KABUPATEN SEMARANG - Asrofah, Siti; Hardati, Puji; Indrayati, Ariyani (Geo-Image, 2017)
This research aims: 1) to know the level of fertility in the Village Bandarjo and Keji Village in the West Ungaran Distric 2) to know the factors that affact the fertility in the Village Bandarjo and Keji Village in the West Ungaran Distric 3)to know the factors that most influential to the level of fertility in the village Bandarjo and Keji village in the West Ungaran Distric. Research methods is research metods descriptive qualitative and quantitative, with research object is fertility. Technical analysis of data used in the study is calculate the fertility and descriptive analysis. The result of the study showed GFR in the Village Bandarjo of 58 babies / year and Keji Village of 38 babies/ year. Factors influencing the fertility rate in Village Bandarjo and Keji Village West Ungaran Districts is first mating age, the number of family members, the level of education and family income. While the use of contraceptives did not affect fertility rate.